On the Acquisition of English Voiceless Stop VOT by Indonesian-English Bilinguals: Evidence of Input Frequency - Evynurul Laily Zen (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
The paper attempts to investigate the acquisition of Voice Onset Time (VOT) of voiceless stop consonants of English /p/, /t/, and /k/ by Indonesian-English bilingual children in its close relation to how second language (L2) input shapes the L2 VOT production. It looks at two different groups of children with native and non native input environment; (1) one 6-years-old girl receiving extensive exposures of English natives from YouTube in about 8 hours per day since she was two in addition to having interactive communication in English with her family members (2) four students (aged 7-8 years old) enrolling in English Partial Immersion Program with non-native environment of English. The comparative analysis concludes that the VOT values differ significantly across different inputs. The children with non native input acquired much shorter VOTs falling within the average of 28 – 36 ms, while those with native input could achieve native-like VOTs in the average of 69 ms for /p/ and /t/ and even longer for stop consonant /k/.